2014
DOI: 10.1080/09638180.2014.976055
|View full text |Cite
|
Sign up to set email alerts
|

On the Effectiveness of Incentive Pay: Exploring Complementarities and Substitution between Management Control System Elements in a Manufacturing Firm

Abstract: Extant research already emphasises that complementarities and substitution involving incentive pay and other elements of an organisation's management control system play an important role in terms of explaining the effectiveness of incentive systems. Despite this awareness calls continue for more research addressing the need to better understand how interdependencies arise among management control system elements and how they affect organisational effectiveness. Based on an indepth case study on the implementa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(53 citation statements)
references
References 40 publications
1
44
0
8
Order By: Relevance
“…The level of aggregation could also be an issue. Gaining a deeper understanding of interdependence between MC practices may require an analysis of more specific attributes (Friis et al, 2014;Grabner & Moers, 2013). For example, this study uses a single measure for the method of incentive determination, yet managers can incorporate subjectivity in a number of ways: subjective weightings on objective measures, use of discretionary bonuses, subjective evaluations of qualitative task dimensions, or subjective evaluations of non-task related dimensions (Gibbs et al, 2004;Grabner, 2014;Höppe & Moers, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The level of aggregation could also be an issue. Gaining a deeper understanding of interdependence between MC practices may require an analysis of more specific attributes (Friis et al, 2014;Grabner & Moers, 2013). For example, this study uses a single measure for the method of incentive determination, yet managers can incorporate subjectivity in a number of ways: subjective weightings on objective measures, use of discretionary bonuses, subjective evaluations of qualitative task dimensions, or subjective evaluations of non-task related dimensions (Gibbs et al, 2004;Grabner, 2014;Höppe & Moers, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Marginson (2002) scrutinized the function of MC elements in a strategy process in a for-profit firm, and focused on the use of different 'categories' of MC elements. More recently, Friis et al (2015) studied different types of relations between incentive systems and other MC elements in a manufacturing firm. Prior research suggested that coupling theory could be useful in studying relations between different organizational phenomena (Beekun and Glick 2001;Orton and Weick 1990;Abernethy and Chua 1996), however, papers that adopt coupling theory to study MC elements are rare.…”
Section: Introductionmentioning
confidence: 99%
“…A major stream of the domain theory on PMS design takes a systems approach (Bedford, Malmi, & Sandelin, 2016;Bracci, Maran, & Inglis, 2017;Malmi & Brown, 2008). An example of the application of systems theory in a qualitative, in-depth, single case study can be found in Friis, Hansen, and Vámosi (2015), who studied the interdependence between elements of control systems. We resonate with the systems theory approach (Boulding, 1956) in our assessment of the success or failure of the PMS.…”
Section: Using Domain Theory To Assess the System As A Success Or Faimentioning
confidence: 99%
“…If they are not, the PMS will fail to provide internal transparency. Thus, our research is not a quantitative contingency theoretical study of 'fit'/'misfit' (Drazin & Van De Ven, 1985), but rather an exploratory systems theory analysis (Bracci et al, 2017;Friis et al, 2015 are other examples of this) of how PMS components produce transparency by examining whether the PMS measures both efficiency and effectiveness.…”
Section: Using Domain Theory To Assess the System As A Success Or Faimentioning
confidence: 99%
See 1 more Smart Citation